Nutritional and growth enhancement of alfalfa sprouts through cold plasma and UV seed treatments - Benabderrahim, Mohamed Ali; Hannachi, Hédia; Elfalleh, Walid; Dufour, Thierry (Italian Journal of Food Science, 2025)
Employing eco-friendly techniques like cold plasma (CP) and ultraviolet (UV) radiation provides innovative approaches to enhance the sprout quality and productivity of alfalfa. This study explores the effects of CP and UV radiation on the germination, growth, and phytochemical profiles of alfalfa sprouts. CP significantly accelerated germination time, reducing median germination time by 8 hours compared to the control, and enhanced photosynthetic pigments, leading to higher biomass (25.87 mg/sprout fresh weight and 1.45 mg/sprout dry weight). UV treatments, particularly UV-C, increased chlorophyll and total flavonoid content. Overall, CP effectively promotes alfalfa germination and growth, while UV treatments improve specific phytochemicals.